2014
DOI: 10.3389/fnhum.2014.00045
|View full text |Cite
|
Sign up to set email alerts
|

Using quantitative and analytic EEG methods in the understanding of connectivity in autism spectrum disorders: a theory of mixed over- and under-connectivity

Abstract: Neuroimaging technologies and research has shown that autism is largely a disorder of neuronal connectivity. While advanced work is being done with fMRI, MRI-DTI, SPECT and other forms of structural and functional connectivity analyses, the use of EEG for these purposes is of additional great utility. Cantor et al. (1986) were the first to examine the utility of pairwise coherence measures for depicting connectivity impairments in autism. Since that time research has shown a combination of mixed over and under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 91 publications
1
39
1
Order By: Relevance
“…Postmortem anatomical inquiries have likewise indicated that the microstructure of cortical circuitry is fundamentally altered in ASD (Casanova et al, 2006; McKavanagh et al, 2015). Investigations examining connectivity on more rapid time scales utilizing electroencephalography (EEG) (Coben et al, 2014) and magnetoencephalography (MEG) (Ye et al, 2014) have similarly indicated that connectivity alterations are a characteristic feature of ASD. These connectivity alterations have been proposed as both a leading biomarker and the origin of the behavioral dysfunction characteristic of the disorder (Geschwind and Levitt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Postmortem anatomical inquiries have likewise indicated that the microstructure of cortical circuitry is fundamentally altered in ASD (Casanova et al, 2006; McKavanagh et al, 2015). Investigations examining connectivity on more rapid time scales utilizing electroencephalography (EEG) (Coben et al, 2014) and magnetoencephalography (MEG) (Ye et al, 2014) have similarly indicated that connectivity alterations are a characteristic feature of ASD. These connectivity alterations have been proposed as both a leading biomarker and the origin of the behavioral dysfunction characteristic of the disorder (Geschwind and Levitt, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Inherent heterogeneity of ASD (Betancur, 2011; Di Martino et al, 2014), maturational processes (Uddin et al, 2013b), task demands (Muller et al, 2011), and data analysis methods (Nair et al, 2014), are all believed to impact indices of functional connectivity and their measurement in ASD. While no consensus has been reached, a mixed profile of long-range hypo-connectivity and local hyper-connectivity has been frequently reported in the literature (Coben et al, 2014; Courchesne and Pierce, 2005; Kitzbichler et al, 2015; Murias et al, 2007; Vissers et al, 2012; Wass, 2011), indicating impaired functional integration and segregation of distributed neural networks in ASD (Rudie et al, 2012). …”
Section: Introductionmentioning
confidence: 99%
“…However, the relation between abnormal circuitry and the behavioral patterns observed in ASD is not straightforward. A recent study showed that standard EEG coherence analysis did not resemble structural connectivity in autism (Coben et al 2014). More advanced approaches to functional and anatomical analysis may provide more detailed and accurate information about the complicated picture of connectivity anomalies in ASD.…”
Section: Autism As a Distributed Disordermentioning
confidence: 99%